Passerini Multi-Component Reaction of Indane-1,2,3-trione, Isocyanides and 2-Furancarboxylic Acid - Reza Kazemizadeh, Ali; Ramazani, Ali (Asian Journal of Chemistry, 2011)
The Passerini reaction of indane-1,2,3-trione, isocyanides and 2-furancarboxylic acid proceed at room temperature and the related α-acyloxycarboxamides is synthesized in quantitative yield. The reactions are one-pot, single spot and the products were obtained without any purification.